Dyke Award Paper. Kinetics of pathologic blood-brain-barrier permeability in an astrocytic glioma using contrast-enhanced MR. - Schmiedl, U P; Kenney, J; Maravilla, K R (American Journal of Neuroradiology, 1992)
PURPOSE The feasibility of measuring blood-brain barrier permeability was studied in a 36B-10 brain glioma model in rats.MATERIALS AND METHODS In stage I of our study, sequential MR images of glioma-implanted rats were obtained following intravenous administration of three contrast agents of different molecular sizes--Gd-DTPA, polylysine-(Gd-DTPA), and albumin-(Gd-DTPA). In a second set of experiments, sequential MR imaging with Gd-DTPA, quantitative measurements of plasma Gd-DTPA concentration, and postmortem tumor Gd-DTPA measurements were used to estimate the blood-to-tissue transport coefficient (Ki) in the rat glioma model at 11 and 15 days postimplantation.RESULTS In stage I, Gd-DTPA caused rapid and greatest tumor enhancement with a significant washout from the tumor during the 120-min experiment. Tumor enhancement using polylysine-(Gd-DTPA) occurred later and was significantly less compared to Gd-DTPA. Tumor signal intensity increased only slowly over time and the peak level of enhancement was least using albumin-(Gd-DTPA). In stage II, the mean (+/- 1 SD) Ki values were 1.1 +/- .24 at 11 days, and 9.3 +/- .8 at 15 days postimplantation. These results correspond well with published data obtained by autoradiography.CONCLUSION We believe that the differential enhancement pattern using contrast agents of different molecular sizes reflects a differential permeability of the pathologic blood-brain barrier, and that our studies demonstrate the feasibility of using frequent sequential images and a graphical approach to Ki calculation to determine the blood-to-tissue transport coefficient using contrast-enhanced MR.